Bioinformatics tools for identifying hepatitis C virus subtypes. - Baclig, Michael O. (Philippine Journal of Science)
With the development of freeware bioinformatics software as well as the availability of web-based software, it is now possible to use various bioinformatics tools to identify viral subtypes such as hepatitis C virus (HCV). This study aimed to demonstrate the role of bioinformatics tools in identifying HCV subtypes and to compare the accuracy of HCV-1 subtyping by 5' UTR PCR-RFLP analysis and DNA sequencing. From a clinical viewpoint, accurate genotype and subtype identification of HCV are important because this may be used as guide for deciding which therapy is appropriate to use for a particular patient. From 2005 up to 2008, we had a total of 30 HCV genotype 1 (HCV-1) positive samples. HCV-1 subtypes were identified by an in-house PCR-RFLP analysis and through direct nucleic acid sequencing using nested primers specific to the 5'UTR and non-structural 5B (NS5B) region. Bioinformatics tools play an important role in identifying HCV-1 subtypes by predicting the size of the amplicon; determining the specific restriction enzyme to cut a given nucleic acid sequence; viewing and editing the electropherogram; aligning nucleotide sequences with prototypes; searching for identical sequences; and understanding the evolution and relationships of various subtypes. The HCV nucleotide sequences reported in this study have been deposited to GenBank. Overall, this information can be utilized to generate molecular diagnostic tests in the future.